Prognostic value of lymphadenectomy in node-negative intrahepatic cholangiocarcinoma: A multicenter, retrospectively study. Issue 4 (April 2023) - Chen, Chen; Su, Jingbo; Wu, Hong; Qiu, Yinghe; Song, Tianqiang; Mao, Xianhan; He, Yu; Cheng, Zhangjun; Zhai, Wenlong; Li, Jingdong; Geng, Zhimin; Tang, Zhaohui
Abstract: Background: This study aimed to evaluate the prognostic value of lymph node dissection (LND) in node-negative intrahepatic cholangiocarcinoma (ICC) and identify the appropriately total number of lymph nodes examined (TNLE). Methods: Data from node-negative ICC patients who underwent curative intent resection in ten Chinese hepatobiliary centers from January 2010 to December 2018 were collected. Overall survival (OS), relapse-free survival (RFS) and postoperative complications were analyzed. Propensity score matching (PSM) was performed to reduce the bias due to confounding variables in LND group and non-lymph node dissection (NLND) group. The optimal TNLE was determined by survival analysis performed by the X-tile program using the enumeration method. Results: A total of 637 clinically node-negative ICC patients were included in this study, 74 cases were found lymph node (LN) positive after operation. Among the remaining 563 node-negative ICC patients, LND was associated with longer OS but not RFS before PSM (OS: 35.4 vs 26.0 months, p = 0.047; RFS: 15.0 vs 15.4 months, p = 0.992). After PSM, patients in LND group had better prognosis on both OS and RFS (OS: 38.0 vs 23.0 months, p < 0.001; RFS: 15.0 vs 13.0 months, p = 0.029). There were no statistically differences in postoperative complications. When TNLE was greater than 8, OS (48.5 vs 31.1 months, p = 0.025) and RFS (21.0 vs 13.0 months, p = 0.043) were longer in the group with more dissected LNs. Conclusion: Routinely LND for node-negative ICC patients is recommended for it helps accurate tumor staging and associates with better prognosis. The optimal TNLE is more than 8.